Compreensões de infância e criança na organização do trabalho pedagógico das professoras da pré-escola - Silva, Natielli Pinheiro da (2024)
The research "Understandings of childhood and children present in the organization of the pedagogical work of preschool teachers", included in the Postgraduate Program in Education - Master's Degree - Area of concentration: Education, Research Line "Culture, educational processes and teacher training", of the State University of Western Paraná - UNIOESTE, aims to analyze the understanding of childhood and children in the organization of the pedagogical work of teachers who work in preschool classes, in a public institution of the municipal network of Francisco Beltrão/PR. This is a Case Study with a qualitative approach of analysis of data, documents, bibliographic material, and application of questionnaires to the subjects selected for the investigation. The instruments used for data production were questionnaires applied to teachers working in preschool in 2023 at the institution researched and the plans for the first week of school classes of the investigated teachers. The questionnaire was organized into three axes: identification; training and professional performance; organization of pedagogical work. The analysis of the plans focused on the objectives, methodological development, and evaluation. In this sense, the analyses were based on the phenomenological perspective and discussion of the theme with Finco (2015); Dahlberg, Pense and Moss (2019); Freitas (1995); Bicudo (1999), Ariès (1986), Sarmento (2007), Malaguzzi (1999), Husserl (2006), Gamboa (2013), among others. The results of the research indicate that the understanding of children and childhood in the organization of pedagogical work in Early Childhood Education (children aged 4 and 5), by teachers of a municipal public institution, includes biological, schooling and preparation aspects for elementary school, highlighting the importance of early childhood education as basic education. This idea is reinforced by the mix of explicit perspectives in the institution's political-pedagogical project